The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.5194/amt-2016-318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement of alkyl and multifunctional organic nitrates by Proton Transfer Reaction Mass Spectrometry

Abstract: Abstract. A commercial PTR-ToF-MS has been optimized in order to allow the measurement of individual organic nitrates in the atmosphere. This has been accomplished by shifting the distribution between different ionizing analytes, H3O+/H3O+(H2O)n or NO+/NO2+. The proposed approach has been proved to be appropriate for the on-line detection of individual alkyl nitrates and functionalized nitrates. It has been shown that hydroxyl- and keto-nitrates have a high affinity towards NO+, leading to the formation of an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…It contains 25 sufficient carbon atoms and oxygen functional groups to likely partition into the condensed phase. NO2 + and C2H4O3 + are known fragments of peroxyacetyl nitrate (PAN) (de Gouw et al, 2003), but NO2 + can also arise from the fragmentation of a wide range of peroxynitrates (ROONO2) or alkyl and multifunctional nitrates (RONO2) (Aoki et al, 2017;Duncianu et al, 2017). While the uptake of PAN on particles can be considered as negligible (Roberts, 2005), higher molecular weight organonitrates are more likely to partition onto the particle phase.…”
Section: Ptr-tof-ms Measurementsmentioning
confidence: 99%
“…It contains 25 sufficient carbon atoms and oxygen functional groups to likely partition into the condensed phase. NO2 + and C2H4O3 + are known fragments of peroxyacetyl nitrate (PAN) (de Gouw et al, 2003), but NO2 + can also arise from the fragmentation of a wide range of peroxynitrates (ROONO2) or alkyl and multifunctional nitrates (RONO2) (Aoki et al, 2017;Duncianu et al, 2017). While the uptake of PAN on particles can be considered as negligible (Roberts, 2005), higher molecular weight organonitrates are more likely to partition onto the particle phase.…”
Section: Ptr-tof-ms Measurementsmentioning
confidence: 99%
“…with H 3 O + ionization, it has been shown that organic nitrates are subject to important fragmentation (Müller et al 2012 ;Aoki, Inomata, and Tanimoto 2007). In order to reduce this fragmentation, Duncianu et al 2017 has adapted the instrument operating procedure for organic nitrate detection by reducing the electric field in the reactor. The same study has also developed a NO + ionization mode, by replacing the ionization gas (water vapor) with dry air and also by applying a reduced electric field.…”
mentioning
confidence: 99%
“…Alkylnitrates fragment severely upon protonation, 63 and the nitric acid ester, (CH 3 ) 2 (NH 2 )CCH 2 ONO 2 , should it be formed on the particles or in the sampling lines, is expected to primarily show up at m / z 88.076 (NO 2 -ejection) and 72.081 (HNO 3 -ejection), whereas the protonated molecule signal at m / z 135.076 should be almost 2 orders of magnitude smaller. The signals at m / z 88.076 and 72.081 also have contributions from 2-amino-2-methylpropanal and AMP, respectively, and it is consequently not possible to resolve by PTR-MS, if 2-amino-2-methylpropyl nitrate, AMPNO 2 , or both are actually formed in the particle phase in the present experiments.…”
Section: Resultsmentioning
confidence: 99%